2009
DOI: 10.1111/j.1748-7692.2009.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of humpback whales (Megaptera novaeangliae) to whale-watching vessels on the southeastern coast of Australia

Abstract: This study assessed the short‐term responses of humpback whales to whale‐watching vessels during their southward migration along the south coast of New South Wales (NSW), Australia. The behavior of pods was recorded from commercial whale‐watching vessels during tours and compared to pods observed in the absence of vessels from the shore in the same area. While some individuals showed obvious signs of horizontal avoidance, others approached vessels, initiating interactions. Calf pods were more sensitive to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 25 publications
(34 reference statements)
8
89
4
Order By: Relevance
“…Southern resident killer whales (Orcinus orca) along San Juan Island, USA, spent more time travelling and less time feeding when whale-watching boats were as far as 1000 m away from the pod ). Humpback whales (Megaptera novaeangliae) also exhibited less feeding behaviour when encountered by whale-watching boats within 1000 m along the south-eastern coast of Australia (Stamation et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern resident killer whales (Orcinus orca) along San Juan Island, USA, spent more time travelling and less time feeding when whale-watching boats were as far as 1000 m away from the pod ). Humpback whales (Megaptera novaeangliae) also exhibited less feeding behaviour when encountered by whale-watching boats within 1000 m along the south-eastern coast of Australia (Stamation et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cetacean-based tourism is one of these growing potential threats and has resulted in increased exposure of dolphin and whale populations to high levels of boat traffic and disturbance (e.g. Bejder et al 2006b;Stensland and Berggren 2007;Stamation et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive management should aim at reducing the number of noise events per boat, which can improve the whale watching experience and reduce the impact on male singing behavior. Stamation et al (2010) found that calf pods were more sensitive to the presence of vessels than non-calf pods, and that dive times and the overall percentage of time whales spent submerged were higher in the presence of vessels. The authors caution that since the long-term impacts of the effects of vessels are unknown, management of the humpback whale-watching industry should adopt a conservative approach.…”
Section: Sustainable Practicesmentioning
confidence: 90%
“…Meanwhile, whale watching tour to see humpback whales had begun in New England and Hawaii in 1975 and is expanding all over the world since then (Hoyt 2001). As the whale watching industry grows, the concern over negative impact on whales being watched also grows (Tilt 1987;Beach and Weinrich 1989;Corkeron 2004;Stamation et al 2010). There are some reports suggesting that the behavioral changes of whales can be induced by close approach of tourist vessels (Williams et al 2002;Lusseau 2003;Scheidat et al 2004).…”
mentioning
confidence: 99%
“…These reports also indicate that females with a calf are more sensitive and susceptible to vessel disturbance *To whom correspondence should be addressed. E-mail: n-kobayashi@okichura.jp than whales without a calf (Bauer 1986;Stamation et al 2010). The Large Whale Ship Strike Database shows that approximately 14% of the collisions between ships and whales in the United States of America are associated with whale watching vessels (Jensen and Silber 2003).…”
mentioning
confidence: 99%